Comparative analysis of cytosolic and mitochondrial ATP synthesis in embryonic and postnatal hippocampal neuronal cultures - Surin, Alexander M.; Khiroug, Serguei; Gorbacheva, Lubov R.; Khodorov, Boris I.; Pinelis, Vsevolod G.; Khiroug, Leonard (Frontiers in Molecular Neuroscience, 2013)
ATP in neurons is commonly believed to be synthesized mostly by mitochondria via oxidative phosphorylation. Neuronal mitochondria have been studied primarily in culture, i.e. in neurons isolated either from embryos or from neonatal pups. Although it is generally assumed that both embryonic and postnatal cultured neurons derive their ATP from mitochondrial oxidative phosphorylation, this has never been tested experimentally. We expressed the FRET-based ATP sensor AT1.03 in cultured hippocampal neurons isolated either from E17-18 rat embryos or from P1-P2 rat pups and monitored [ATP]c simultaneously with mitochondrial membrane potential (ΔΨm; TMRM) and NAD(P)H autofluorescence. In embryonic neurons, transient glucose deprivation induced a near-complete decrease in [ATP]c, which was partially reversible and was accelerated by inhibition of glycolysis with 2-deoxyglucose. In the absence of glucose, pyruvate did not cause any significant increase in [ATP]c in 84% of embryonic neurons, and inhibition of mitochondrial ATP synthase with oligomycin failed to decrease [ATP]c. Moreover, ΔΨm was significantly reduced by oligomycin, indicating that mitochondria acted as consumers rather than producers of ATP in embryonic neurons. In sharp contrast, in postnatal neurons pyruvate added during glucose deprivation significantly increased [ATP]c (by 54±8%), whereas oligomycin induced a sharp decline in [ATP]c and increased ΔΨm. These signs of oxidative phosphorylation were observed in all tested P1-P2 neurons. Measurement of ΔΨm with the potential-sensitive probe JC-1 revealed that neuronal mitochondrial membrane potential was significantly reduced in embryonic cultures compared to the postnatal ones, possibly due to increased proton permeability of inner mitochondrial membrane. We conclude that in embryonic but not postnatal neuronal cultures ATP synthesis is predominantly glycolytic and the oxidative phosphorylation-mediated synthesis of ATP by mitochondrial ATPase is insignificant